2019
DOI: 10.1177/0218492319853733
|View full text |Cite
|
Sign up to set email alerts
|

Horner syndrome due to blunt thoracic trauma

Abstract: A relationship between Horner syndrome and thoracic trauma is exceedingly rare. We present the case of a 46-year-old man who was brought to our center after an accidental fall from a height of 4 meters. He sustained multiple ribs fractures as well as scapular and clavicle fractures in the left hemithorax. During his hospital stay, he developed Horner syndrome due to a posterior fracture of the first rib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…The fracture site was beside the thoracic outlet and relatively close to the lung apex, where the bony fragment, swollen soft tissue, or a hematoma might cause an interruption or compression of the second-order neuron, leading to preganglionic Horner's syndrome (Figure 4). All cases of traumatic Horner's syndrome, or iatrogenic Horner's syndrome, mentioned in the literature are summarized in Table 1 (6)(7)(8)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Karen et al reported osteochondroma of the clavicle, which, although rare, should be considered in the differential diagnosis of causes of Horner's syndrome (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture site was beside the thoracic outlet and relatively close to the lung apex, where the bony fragment, swollen soft tissue, or a hematoma might cause an interruption or compression of the second-order neuron, leading to preganglionic Horner's syndrome (Figure 4). All cases of traumatic Horner's syndrome, or iatrogenic Horner's syndrome, mentioned in the literature are summarized in Table 1 (6)(7)(8)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Karen et al reported osteochondroma of the clavicle, which, although rare, should be considered in the differential diagnosis of causes of Horner's syndrome (10).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if the nerve is compressed for a longer period, the time to recovery is longer. None of the patients mentioned in the literature who had Horner's syndrome with a first rib fracture received an operation (6,(14)(15)(16)(17)19), and neither did the patient with a clavicle and third rib fracture (18). Most patients took an extended period to recover, some with no improvement, and one even needed ophthalmological surgery (18).…”
Section: Discussionmentioning
confidence: 99%
“…Ancak adli pratikte etiyolojideki travma ve cerrahi girişimlere bağlı daha nadir nedenler görülmektedir. Örneğin literatürde servikal cerrahi sonrasında %0,006 gibi nadir bir oranda görüldüğü ( 4) ve travmatik 1. kot kırığına sekonder bildirilmiş sadece sekiz olgu olması oldukça dikkat çekicidir (3). Adli olgularda travma künt ya da penetran özellikte olabilir.…”
Section: Discussionunclassified
“…Adli olgularda travma künt ya da penetran özellikte olabilir. Anatomik bütünlüğün bozulduğu ve genellikle cerrahi müdahale gerektiren penetran travmalarda HS ortaya çıkma olasılığı daha yüksektir (3). Adli açıdan HS'da dikkat edilmesi gereken bir nokta, etiyolojisinde malign tümörler başta olmak üzere birçok ayırıcı tanı içermesi sebebiyle illiyet kurulmadan önce altta yatan başka bir hastalığa işaret eden durum olmadığından emin olmaktır.…”
Section: Discussionunclassified
See 1 more Smart Citation